1986
DOI: 10.1042/bj2370175
|View full text |Cite
|
Sign up to set email alerts
|

A spectrophotometric assay for superoxide dismutase activities in crude tissue fractions

Abstract: A sensitive and reliable assay method was developed to characterize crude cell homogenates and subcellular fractions with regard to their superoxide dismutase (SOD) activities. The determination of SOD activities was based on the well-known spectrophotometric assay introduced by McCord & Fridovich [(1969) J. Biol. Chem. 244, 6049-6055], with partially succinylated (3-carboxypropionylated) rather than native ferricytochrome c as indicating scavenger. Partial succinylation of cytochrome c resulted in minimizatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
43
0
1

Year Published

1990
1990
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(44 citation statements)
references
References 23 publications
0
43
0
1
Order By: Relevance
“…SOD plays an important role in protecting the cell against the potentially toxic effects of environmental pollutants (Kuthan et al, 1986). In the present study, hepatic SOD activity was significantly decreased with the increasing dietary Cd levels.…”
Section: Enzyme Activities In Serum and Livermentioning
confidence: 95%
“…SOD plays an important role in protecting the cell against the potentially toxic effects of environmental pollutants (Kuthan et al, 1986). In the present study, hepatic SOD activity was significantly decreased with the increasing dietary Cd levels.…”
Section: Enzyme Activities In Serum and Livermentioning
confidence: 95%
“…Moreover, the authors reported that high-dose Ad.SOD2 gene delivery in rats prevented ischemia/reperfusion injury by inactivation of nuclear transcription factors NF-B and AP-1 (11). In contrast, in the liver transplantation model, Cu/Zn-SOD was selected because it represents the predominant isoform in the liver (12). Gene delivery of the Cu/Zn-SOD leads to a significant increase in SOD activity in transplanted livers, minimizes injury, and increases survival (9,10).…”
Section: Ischemia/reperfusion Injury Of Livers: Role Of Different Isomentioning
confidence: 98%
“…Next, the cytochrome C reduction rate was measured in the presence of the sample (23). The difference between the two rates was attributed to SOD being present in the tested sample.…”
Section: Animal Model and Experimental Design Eight-week-old Malementioning
confidence: 99%